Customizing chef - Cowie, Jon 1983- (O'Reilly, 2014)
Annotation
Includes index. - Online resource; title from PDF title page (ebrary, viewed September 3, 2014)
Keywords: Chef (Computer program); Technological innovations -- Management; Innovations; Gestion; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference; Technological innovations; Management